ANALISIS PENGELOLAAN DAN PERTANGGUNGJAWABAN KEUANGAN KAMPUNG (Studi Empiris pada Distrik Sentani Kabupaten Jayapura) - Dewi Rasmi; Agustinus Salle; Bill J.C Pangayow (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
The purpose of this study is to examine accounting issue particularly in the view of village financial management and the accountability constraints experienced by village heads in managing village finances. This research was conducted at Sentani District of Jayapura District. The number of samples was taken as much as 45 respondents-apparatus kampung. This study uses purposive sampling method by distributing questionnaires to respondents. Analytical technique using SmartPLS (Partial Least Square). The results of this study indicate that accountability in the view of village financial management and constraints in the accountability of village heads has no significant effect on village financial management.